From bilateralism to community interest essays in honour of Bruno Simma - Fastenrath, Ulrich; Simma, Bruno (Oxford : Oxford University Press, 2011)
Tracing the development of international law from regulating bilateral state-to-state relationships towards the promotion of the international community and the protection of human rights this book, dedicated to the work of Judge Bruno Simma, forms a significant contribution to the theory and practice of international law.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: International law; International relations; Human rights; International law -- History